Tampering by office-based methadone maintenance patients with methadone take home privileges: a pilot study - Frank Nathan; Emadi-Konjin Pasha; Worster Andrew; Raz Barak; Daiter Jeff; Teplin David; Varenbut Michael; Konyer Alan; Greenwald Iris; Snider-Adler Melissa (BMC, 2007)
Abstract Methadone Maintenance Treatment (MMT) is among the most widely studied treatments for opiate dependence with proven benefits for patients and society. When misused, however, methadone can also be lethal. The issue of methadone diversion is a major concern for all MMT programs. A potential source for such diversion is from those MMT patients who receive daily take home methadone doses. Using a reverse phase high performance liquid chromatography method, seven of the nine patients who were randomly selected to have all of their remaining methadone take home doses (within a 24 hour period) analyzed, returned lower than expected quantities of methadone. This finding suggests the possibility that such patients may have tampered with their daily take home doses. Larger prospective observational studies are clearly needed to test the supposition of this pilot study.